The Role Of Nature-Based Learning In Developing Early Childhood Creativity - Suryadi Suryadi (FKIP UNSULTRA, 2025)
Nature based learning has become an increasingly popular approach in early childhood education due to its potential in stimulating children's creativity. This study aims to analyze the role of nature-based learning in developing early childhood creativity through a literature study. The method used is a literature review of various relevant studies and theories. The results of the study indicate that nature-based learning provides a multisensory experience that can enrich children's imagination and creativity. Exploratory activities such as playing with natural materials, observing natural phenomena, and interacting with the surrounding environment have been shown to improve children's creative thinking skills. In addition, nature-based learning also strengthens the social-emotional aspects that contribute to the development of creativity. The conclusion of this study shows that the integration of nature-based learning in the early childhood education curriculum is very necessary to optimize the development of children's creativity.